Editorial: Dislodging Girlhood?. Issue 1 (1st March 2019) - Mitchell, Claudia
Abstract : I am very grateful to Barbara Brickman, the guest editor of this Special Issue of Girlhood Studies: An Interdisciplinary Journal for her term "dislodging girlhood" in the context of heteronormativity. Repeatedly in this issue Marnina Gonick's pivotal question, "Are queer girls, girls?" (2006: 122) is cited. In the 13 years since she posed this question, we have not seen enough attempts made to address it. To mix my metaphors I see this issue of Girlhood Studies as helping to break the silence and simultaneously to open the floodgates to a ground-breaking collection of responses to Gonick's question. Given the rise of the right in the US and in so many other countries, queer girls— trans, lesbian, gender non-conforming, non-binary to mention just a few possibilities—are at even greater risk than before. Girlhood Studies has always been concerned with social justice, so this special issue is a particularly important one in our history. It is also worth noting that many of the articles are written or co-authored by new scholars, signaling an encouraging trend in academic work that has social justice at its core. I thank Barbara Brickman, the authors, and the reviewers for their history-making contributions to the radical act of dislodging girlhood.